Προσομοιώσεις Monte Carlo σε νανοκρυσταλλικό πυρίτιο για ηλιακές εφαρμογές - Νεοφύτου, Χριστίνα (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2013)
The subject of the present final year project report is the investigation of structural properties and stability of nanostructured silicon. For this purpose, various structures have been developed and simulated with the statistical method of Monte Carlo in conjunction with empirical potentials for the calculation of energy. The system under study is a nanocomposite made of Si nanocrystals embedded in hydrogenated amorphous silicon (Si-nc/a-Si:H). It is found that the formation energy of the nanocomposite reduces with increasing distance between the nanocrystals, indicating higher stability of the system. The striking finding of this study is that these nanocomposites are stable at even very close distances between the nanocrystals. Thus, it is possible to to use such structures for solar cell applications, where it is desirable to have the nanostructures located at close distances for more efficient extraction, separation and transport of the photogenerated carriers.
Keywords: Nanostructured Silicon; Method of Monte Carlo; Si Nanocrystals; Νανοδομημένο Πυριτίο; Προσομοίωση Monte Carlo; Νανοκρυστάλλα Πυριτίου